Industrial electronics [Technology 2000 analysis and forecast]. - Kaplan, G.
Energy savings and higher intelligence are hallmarks of today's highly competitive world of industrial automation. While power electronics devices and systems deliver ever more watts, they also contribute to electromagnetic interference (EMI), and users are becoming aware of the need to increase their overall system reliability. Teetering on the verge of acceptance are easily programmable service robots, automatically cleaning their way around public facilities. At the same time, researchers are exploring the possibility of using magnetic resonance imaging (MRI) technology on the factory floor. Both the water content of products and their material hardness are being analyzed by MRI scans to monitor product quality. For embedded systems designers, who have the complex task of testing and debugging embedded processors, relief is in the offing with a new, global standard. The standard, for a device interface for embedded processors, should simplify the testing and debugging of the processors used in such fields as automotive electronics, aerospace, telecommunications, appliances, and consumer electronics. Simplifying those tasks ought to shorten the time to market of products and systems in most, if not all, of these areas
Keywords: EMI; MRI; Aerospace; Automatic cleaning robots; Automotive electronics; Consumer electronics; Electromagnetic interference; Embedded processors; Energy savings; Industrial automation; Intelligence; Magnetic resonance imaging; Material hardness; Power electronics devices; Processors debugging; Product quality monitoring; Programmable service robots; System reliability increase; Technology forecast; Telecommunications; Water content